Penerapan Intervensi Cold Pack Terhadap Penurunan Skala Nyeri Pada Pasien dengan Post Op ORIF di Bangsal Bougenvile RSUD Kota Yogyakarta - Lusiyani Rahayu Mayanti; Retno Sumiyarini (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Fracture is a condition of partial or total loss of cartilage continuity caused by trauma or physical force. The high incidence of fractures each year requires appropriate management including fracture surgery, namely Open Reductive Internal Fixation (ORIF)—one of the problems that occurs after ORIF is pain. Pain is an unpleasant emotional and physiological phenomenon. Pain can be treated with non-pharmacological therapies, including a cold compress with a cold pack. Objective: To determine the decrease in pain scale with non-pharmacological therapy (cold pack compress). Methods: The method used in this case study is a pretest-postest design. Researcher compared the patient's condition before and after treatment of cold pack. Intervention was carried out for three consecutive days with administration twice daily for 20 minutes. The instruments used in this case study are assessment sheets and pain scale measurement observation sheets using the Numeric Rating Scale (NRS). Results: Before being given a cold pack compress, Mr. A's pain scale was moderate (scale 5). After being given three consecutive days of action, patient’s pain scale decreased to mild (scale 1). Conclusion: The application of cold pack intervention effectively reduces the pain scale in ORIF post-op patients.